Behavioral health integration in a nurse-led federally qualified health center: Outcomes of care. Issue 12 (7th December 2021) - Weber, Mary; Stalder, Sarah; Techau, Aimee; Centi, Sophia; McNair, Bryan; Barton, Amy J.
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: Background: Over the past 20 years, significant evidence has emerged for collaborative care in the treatment of depression and anxiety disorders in primary care. Purpose: The purpose of this project was to integrate an interprofessional and collaborative care model of behavioral health services into routine nurse-led primary care delivered to vulnerable and underserved populations across the lifespan. Team members included psychiatric nurse practitioners (PMHNPs), a registered nurse, and a case manager. Methods: An Access database was developed to track clients seen by the PMHNPs. Three key outcome measures were tracked over time: Posttraumatic Stress Disorder (PTSD) Checklist Civilian Version, Hamilton Depression Rating Scale (HAM-D), and Bipolar Depression Rating Scale (BDRS). A retrospective analysis of client outcome data from January 2017 through December 2019 was conducted. Results: There were 118 patients included who were mostly female (63.6%), White (90.7%), and not Hispanic (69.5%), with Medicaid as their primary insurance (74.6%). For each outcome, models with linear and quadratic function forms for time were fit. The final model for PTSD Checklist Score had a linear functional form for time and the final models for BDRS and HAM-D had linear and quadratic terms for time. All predictors were significantly associated with the outcome. Implications for practice: This program demonstrated that a patient-centered, nurse-led team approach to the treatment of depression, bipolar depression, and PTSD can be successful in primary care.